PENERAPAN METODE K-MEANS UNTUK PENGELOMPOKAN TINGKAT KEPUASAN PENGGUNA LULUSAN PADA TRACER STUDY PUSAT KARIR ITN MALANG - Widhi Nugraha, Brilliananda; Mahmudi, Ali; Santi Wahyuni, Febriana (Institut Teknologi Nasional Malang, 2021)
The National Institute of Technology Malang is one of the well-known private universities in Indonesia so that it has many students from various regions in Indonesia, as well as its alumni. Career Center of the National Institute of Technology Malang as one of the infrastructure facilities that provides various services ranging from information on job availability to pre-employment information in the form of training and internships that are useful for students and alumni of ITN Malang. Career Center ITN Malang has played a major role in supporting students in the academic process. To determine the quality of alumni, tracer studies can be used to determine the progress of alumni after entering the workforce. In this research, research and development is carried out based on website applications, the method used is the K-Means method, the requirements for the thesis product developed include a system that can only be used on a computer device, the system is only accessed by ITN Malang Career Center officers. This research is about the Analysis of Tracer Alumni of the National Institute of Technology Malang in 2020 using the K-Means algorithm using the PHP and MySQL programming languages. The results of this study are products in the form of website applications, products have features, namely the system on the website can provide alumni quality analysis based on graduate user tracer study data, users can enter alumni user satisfaction data from tracer study data from criteria namely ethics, scientific expertise, expertise outside of science , English language skills, technology skills, communication skills, collaboration skills, independent work skills, competency skills and to determine competency data with criteria including student identification number, study program, knowledge of science, knowledge outside of science, English language skills, ability computers, communication skills, independence, teamwork, development skills, based on functional testing of the system for features - all of them were successful and running well, based on the research concluded that all features can run well on browsers namely Microsoft Edge 91.0.864.59, Mozilla Firefox 89.0.2 and G oogle Chrome 91.0.4472.114, based on user testing the majority rate very good on the use of the application.